UiTMCPP English language club AGM 2021 / Nur Afiqah Abdul Latif, Noor Azli Affendy Lee and Nur Ilianis Adnan - Abdul Latif, Nur Afiqah; Affendy Lee, Noor Azli; Adnan, Nur Ilianis (Academy of Language Studies, 2021)
This is the second year for the English Language Club of UiTM Cawangan Pulau Pinang (UiTMCPP) to hold the Annual General Meeting (AGM) through Google Meet. It was held on 16 July 2021 (9.00 p.m. to 10.00 p.m.). The meeting was chaired by the Vice President of the club, Anis Nabilah Mohd Razib and minuted by Irdina Izman. The meeting agenda includes the presentation of activities conducted by the club in 2020/2021, a farewell speech by Madam Nur Afiqah Ab. Latif (the club advisor) and the election for the new club Executive Members (MTs). The meeting began with a prayer recitation by Amzar Syakir Asmadi followed by an opening speech by the president of the club, Ammar Najmi Ahmad Anuar. It then continued with a farewell speech by Madam Nur Afiqah who will end her tenure as the club advisor in October 2021. Subsequently, each programme leader presented the club activities in 2020/2021.